Modified pulmonary artery banding: A novel strategy for balancing pulmonary blood flow with transposed great arteriesCentral MessagePerspective - Gananjay G. Salve, MS, MCh; Andrew D. Cole, BAppSci (Hon); Ian A. Nicholson, FRACS; David S. Winlaw, MD, FRACS; Richard B. Chard, FRACS; Yishay Orr, PhD, FRACS (JTCVS Techniques)
Objective: To study the outcomes of a novel modified pulmonary artery banding (mPAB) technique used for staged repair of a subset of patients with complex transposition physiology. Methods: A total of 13 patients who underwent mPAB during their staged repair (biventricular repair [BVR], n = 6) or palliation (1-1/2 repair, n = 1; univentricular repair [UVR], n = 6) from 2004 to 2020 were studied retrospectively. A restrictive interposition graft was used to reconstruct the main PA between the pulmonary root and the distal pulmonary confluence, functioning as a mPAB. Twelve of the 13 patients (92.3%) underwent a concurrent arterial switch operation (ASO), of which 6 were palliative ASOs for 1-1/2 repair (n = 1) or UVR (n = 5). Patient weight and cardiac anatomy determined the size of interposition graft. Results: The disease spectrum included dextro transposition of the great arteries (d-TGA) with multiple ventricular septal defects (VSDs) (n = 4), Taussig–Bing anomaly (n = 3), d-TGA with VSD and hypoplastic right ventricle (RV) (n = 3), double-inlet left ventricle with l-TGA (n = 2), and congenitally corrected TGA with double-outlet RV (n = 1). The Lecompte procedure was performed in 10 patients. Predischarge echocardiography revealed a band gradient of 61 mm Hg (interquartile range [IQR], 40-90 mm Hg) for BVR/1-1/2 ventricular repair (n = 7) and 49 mm Hg (IQR, 37-61 mm Hg) for UVR (n = 6). Survival was 100% at a median follow-up of 3.7 years (IQR, 2.6-4.0 years). Conclusions: The mPAB technique is effective and reproducible for staged BVR or UVR for patients with TGA. It effectively regulates pulmonary blood flow, may reduce neopulmonary root distortion, and eliminates complications associated with band migration in standard PAB.